Using Psychology in the Classroom - Minton Stephen James (Sage Publications, 2012)
This book is vital reading for all those studying psychology and Applied Psychology in primary and secondary teaching degree programs. Acknowledgements, Introducing Psychology in the Classroom, An Overview of Child and Adolescent Psychological Development, The Self-Esteem and Self Esteem Enhancement Through Educational Practice, Intelligence and Learning Styles and Educational Attainment, Positive Discipline and Conflict Resolution and Co-Operative Learning, Thinking about Special Educational Needs, Preventing and Countering Bullying Behavior and Cyber-Bullying in Schools, Dealing with Prejudice and Racism and Homophobia and Alterophonia in Schools, Stress and Stress Management for Teachers and Educators, Conclusions, References, Index.